The changing face of Korean management - Rowley, Chris, 1959; Paik, Yongsun, 1956 (London ; New York : Routledge, 2009)
Part of the successful Routledge "Working in Asia" series, "The Changing Face of Korean Management" focuses on a country that is predicted by some experts to become the world's third richest by 2025. South Korea, with its thriving telecommunications and automotive industries, and increasing trade links with China, survived the 1997 Asian Economic Crisis better than most. This important textbook explores the key areas of management in this pivotal country in the region, including: Human Resource Management; Marketing Operations; Finance Strategy; Overseas affiliates; Small firms and entrepreneurship; and, Women. Including case studies and interviews with front-line Korean managers to enable a real 'voice' to emerge, and written by native academics, this is a complete analysis of the current state of management structures in South Korea. It is an important reading for all students of business and management interested in Asia.
Setting the scene for the changing face of South Korean management / Chris Rowley and Yongsun Paik -- The changing face of Korean human resource management / Gyu-Chang Yu and Chris Rowley -- The changing face of Korean marketing management / Changjo Yoo and Robert D. Winsor -- The changing face of operations management in Korea / Joon-Soo Jon, Eui Hong and Byung-Gak Son -- The changing face of Korean finance management / Won Kang -- The changing face of Korean strategic management / Seung-Hyun Lee and Sang-Myung Lee -- The changing face of Korean small and medium-sized enterprises management / David Y. Choi, Susan Elkinawy and Stacey H. Wang -- The changing face of Korean management of overseas affiliates / Yongsun Paik and Yong Suhk Pak -- The changing face of Korean women in management / Namhee Kim and Chris Rowley -- The changing face of Korean management revisited / Yongsun Paik and Chris Rowley
Includes bibliographical references and index.
Keywords: Management -- Korea (South).; Organizational change -- Korea (South).; Corporate culture -- Korea (South).; Samfundsbeskrivelser; Management; Sydkorea